2019
DOI: 10.2147/ppa.s206728
|View full text |Cite
|
Sign up to set email alerts
|

<p>Factors Influencing Participation Of Healthy Volunteers In Clinical Trials: Findings From A Cross-Sectional Study In Delhi, North India</p>

Abstract: PurposeTo identify the specific motivations that drive healthy volunteers to consent for their participation in clinical studies. Additionally, the study aimed to document the socio-demographic determinants of participation in the trial related solely to the intention of securing financial gains.Patients and methodsThis cross-sectional study was conducted among subjects who participated as healthy volunteers in clinical trials conducted by Contract Research Organizations (CROs) of Delhi. Pre-tested, validated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
(41 reference statements)
2
6
0
Order By: Relevance
“…Several participants in this study mentioned access to free full medical check-ups as one of the advantages of participating in the clinical trial. The results of this study are consistent with other studies exploring the motivation factors for healthy participants to take part in clinical trials [ 51 , 54 ]. Many of these participants considered the medical check-up performed as a requirement for the Phase I screening process for the early phase clinical trials a benefit because it confirms their health status.…”
Section: Discussionsupporting
confidence: 91%
“…Several participants in this study mentioned access to free full medical check-ups as one of the advantages of participating in the clinical trial. The results of this study are consistent with other studies exploring the motivation factors for healthy participants to take part in clinical trials [ 51 , 54 ]. Many of these participants considered the medical check-up performed as a requirement for the Phase I screening process for the early phase clinical trials a benefit because it confirms their health status.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, financial compensation was reported an encouraging factor for those that previously participated in a CT, while it does not affect the attitudes of participation-naïve individuals. 26,27 In the present study, the results demonstrated confidence of respondents in the Jordanian healthcare system and being comfortable from their physician's positive belief in a CT. A moderate positive correlation was found in the current study between knowledge and perception in regards to CTs. Jordan has a well-developed and reputable healthcare system, attributed mainly to the relative high physician to population ratio and the well-equipped hospitals.…”
Section: Discussionsupporting
confidence: 60%
“…Detailed analysis demonstrated respondents that previously took part in a CT were more affected by financial compensation compared with those that never participated (data not shown). Similarly, financial compensation was reported an encouraging factor for those that previously participated in a CT, while it does not affect the attitudes of participation‐naïve individuals 26,27 …”
Section: Discussionmentioning
confidence: 99%
“…Finally, factors such as age (Sheikh & Mattingly, 1981;Teschke et al, 2010;Van Wieren-de Wijer et al, 2009), race/ethnicity (Braunstein et al, 2008;Liu et al, 2019;Milani et al, 2020;Shavers et al, 2002;Webb et al, 2019;Wendler et al, 2006), time constraints (Markanday et al, 2013;Stuart et al, 2019), and financial compensation (Bentley & Thacker, 2004;Ding et al, 2007;Grady, 2005;Ranjan et al, 2019) sometimes correlate with or impact willingness to participate in research. Future research can examine if these factors also influence participation in specific ESS procedures and if they interact with sex to impact participation.…”
Section: Future Researchmentioning
confidence: 99%